General Competencies in Undergraduate. Teacher’s Perception of their Development from the Tutorial Action - Carrasco Reyes, Percy Rogelio; Álvaro Fernández, Delcy Gladis; Cruz Cervantes, Jesús Manuel; Chayña Aguilar, Luis (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The purpose of the study that will end this article was to analyze the perceptions of coordinators and tutor teachers on the development of general skills in undergraduate students from the tutorial action. The study was carried out according to the qualitative approach and phenomenological design, whose population was made up of coordinators and tutors of undergraduate students from a University of Lima from their experiences in the tutorial action. The sample size will be extended due to the saturation criterion. The data was collected through a structured survey guide and scientific rigor was oriented according to quality criteria: reliability, transferability, dependency and confirmability. It was found as a main result that the tutorial action contributes to the development of some generic skills, such as written and oral communication, and teamwork, which are the most valued by the tutorial experience, since fluid and assertive communication is required. for collaborative work.